Pelatihan Public Speaking bagi Worship Leader pada Jemaat dan Pemuda Gereja Pantekosta di Indonesia (GPdI) ‘Betlehem’ Sungai Rengas - Sibatuara, Udur Delima; Windy, Windy (Amare, 2022)
The ability to speak in public is known as public speaking. Public speaking can take many forms, including speeches, lectures, and presentations, as well as becoming a master of ceremony (MC) or event guide. Becoming a master of ceremony (MC) or an event guide is not easy; it takes a lot of practice and experience to perform well. This is because the ability to host a show is a soft skill that can be developed through continuous training and development. Many difficulties are encountered during its implementation, ranging from nervousness, fear, tension, and so on. Based on the reported of the eservice leader that Worship leaders among the congregation and youth at Gereja Pantekosta di Indonesia (GPdI) Bethlehem, Sungai Rengas. have found often feeling nervous when speaking in front of the congregation, being confused in conveying sentences that easy to understand, and not maximize eye contact, which prevents them from communicating effectively with musicians. As a result, the committee invited the team Pengabdian kepada masyarakt (PkM) to provide workshops that could be used later when the worship leaders were in charge of guiding the church services.